Torsional effects of a novel rebar stiffened cold-formed U-shaped steel-concrete composite beam system. (1st April 2020) - Zhao, Yi; Zhou, Xuhong; Yang, Yuanlong; Liu, Jiepeng; Chen, Yohchia Frank
Graphical abstract: Highlights: A novel cold-formed U-shaped steel-concrete composite beam (RCUCB) is studied experimentally. A typical torsional failure was observed in the experiment. Influencing factors on stiffness and torque capacity are determined. The calculation methods for elastic stiffness, cracking torque capacity, and ultimate torque capacity of RCUCB are proposed. Abstract: Torsional effects of a novel rebar stiffened U-shaped steel-concrete composite beam (RCUCB) system are discussed in this paper, based on a series of torsional experiments. The rebar truss is welded on the top varus flanges of the open steel U-section to enhance its stability; The inverted U-shaped rebar is furnished to enhance the integral action between concrete slab and beam web; and the bottom rebar is installed to control the interface slip between concrete and steel. The test results reveal that the torsional failure mode of RCUCB is characterized by the critical inclined concrete cracks and crushed inclined struts of the slab, the cracking torsion ratio ( ψ cr, b ) is 0.04–0.05 ψ u, b, the cracking torque capacity ( T cr ) is 0.31–0.44 T u, and the secant stiffness at the ultimate load is 13–25% of the elastic stiffness. Additionally, some influencing factors are found: the elastic stiffness and cracking torque capacity increase with increasing slab width, slab thickness, and web depth; the ultimate torque capacity may be improved by increasing slab width, slab thickness, slab reinforcement strength, web depth, rebar truss, and inverted U-shaped rebars. Moreover, the concrete slab and beam web share a common torsion ratio provided that the inverted U-shaped rebars are adequate; and the crack width in the slab can be controlled by the torsion resisting ability of slab and the restraint action from the beam web. Lastly, design methods for elastic torsional stiffness, T cr, and T u of RCUCBs are proposed.